Intraperitoneal haemorrhage- A call for laparotomy as second intervention - Rawal, Suniti; Rana, Ashma; Bista, Kesang D; Gurung, Geeta; Ghimire, Ram K (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Aim: To study laparotomy as second intervention for hemoperitoneum following primary surgery in obstetric and gynecology. Method: Eleven years retrospective study going back from Dec 2006 embracing all the cases of re/laparotomy for intraperitoneal bleeding were carried out in TUTH, Nepal. Results: Of the 24 cases complicated by intraperitoneal hemorrhage for which relaparotomy had been done 12 each were formed by gynaecologic and obstetric cases: 11 were caesareans (CS) and a laparotomy following vaginal birth after caesarean (VBAC). In gynecology the preceding surgeries undertaken were [diagnostic laparoscopy (1), laparotomy (3), hysterectomies 8 (3 being vaginal)] Massive hemoperitoneum occurred in ¼ cases; extensive hematoma in a third having altogether with associated risks factor in 9(37.5%).Source of bleeding were disligated/abraded infundibulopelvic vessel (3), cuff bleeding (4), cardinal ligaments (1), uterine cornua (1), uterine angles (6), vagina (1) and placental bed (1) which were duly managed by 5 obstetrics hysterectomy. Laparotomy >2 times were repeated 4: obstetric 2 [(1) for vault bleeding following hysterectomy done for scar rupture after VBAC and other for slippage of ovarian vessel following hysterectomy and internal iliac ligation] and same number in Gynecology 2 [(1) after vaginal hysterectomy first for laceration of infundibulopelvic vessel and then for generalized ooze and hematoma]. Next was following a diagnostic laparoscopy, complicated by unexplainable intraperitoneal bleeding first devised by internal iliac ligation, then finally by hysterectomy that died. Conclusions: Careful tying of the blood vessel, choosing right technique and appropriate ligature in the first place is as important as proper closure of all the surgical incision/ inflicted cut taking note of the rise in the pulse rate and fall in the blood pressure in overall postoperative cases such that related morbidity and mortality from late diagnosis leading to delayed second surgical intervention can be obviated or minimized. Key Words: Intraperitoneal bleeding, hemoperitoneum, relaparotomy doi:10.3126/njog.v2i2.1458 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 63 - 68